Reevaluating Divorce Rejection in Indonesia's Religious Courts: Integrating maqashid syariah and Human Rights Perspectives - Lina Nur Anisa (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
The phenomenon of the rejection of divorce petitions by Religious Court judges for lawsuits filed by husbands against their wives has sparked significant discourse within the Islamic family law system in Indonesia. Such rejections are influenced not only by formal legal rules but also by considerations of maqashid syariah and human rights principles, particularly in the effort to safeguard family welfare and protect women's rights. This article aims to provide a juridical analysis of the practice of rejecting divorce petitions by Religious Court judges from the perspectives of maqashid syariah and human rights, and to formulate a model for reformulating family law policy that is both responsive and just. This study employs a literature research approach by reviewing primary legal sources, court decisions, and recent relevant journal articles and books. The findings reveal that the rejection of divorce petitions by judges is based on discretionary authority regulated under national legislation and the Compilation of Islamic Law, to maintain mashlahah, prevent harm, and strengthen the protection of women's and children's rights. Further findings emphasise the need for policy reform in family law by integrating maqashid syariah with human rights principles, whether through regulatory reform, judicial training, or strengthening advocacy and protection mechanisms for vulnerable parties. The article concludes that the synergy between maqashid syariah and human rights is a crucial foundation for realising an inclusive, adaptive, and just Islamic family law system in Indonesia.